1979
DOI: 10.1002/micr.1920010308
|View full text |Cite
|
Sign up to set email alerts
|

Absorbable and nonabsorbable sutures in microsurgery: Standardized comparable studies in rats

Abstract: In order to study the applicability and value of synthetic absorbable suture materials in microvascular surgery, 8-0 monofilament nonabsorbable polyamide sutures and 8-0 absorbable polyglycolic acid and polyglactin 910 sutures were used in end-to-end anastomoses of the aorta in rats, employing the same microsurgical model for all procedures. Comparable investigations of the anastomotic sites were carded out macroscopically and histologically at various intervals postoperatively. It was found that when placed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

1980
1980
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 5 publications
0
9
0
1
Order By: Relevance
“…Animal research indicates that the use of absorbable suture may have advantages for the very young patient, possibly decreasing the incidence of long-term foreign body reaction and aneurysm formation. 18, 19 Immediately before beginning the anastomosis, systemic heparin is administered at a dose of 1,000 units for smaller children and 3,000 units for those close to adult weight. If the procedure is lengthy, serial doses of heparin, 500-1,000 units per hour, should be given.…”
Section: Operative Techniquementioning
confidence: 99%
“…Animal research indicates that the use of absorbable suture may have advantages for the very young patient, possibly decreasing the incidence of long-term foreign body reaction and aneurysm formation. 18, 19 Immediately before beginning the anastomosis, systemic heparin is administered at a dose of 1,000 units for smaller children and 3,000 units for those close to adult weight. If the procedure is lengthy, serial doses of heparin, 500-1,000 units per hour, should be given.…”
Section: Operative Techniquementioning
confidence: 99%
“…However, several studies showed that absorbable monofilament (polydioxanone, PDS) or absorbable braided microsuture (polygalactic acid, Vicryl) can be used with comparable results. [8][9][10][11][12] Although comparable, these types of microsutures are very expensive ($30-40 U.S. dollars per piece) and highly consumable materials, especially in new and novice microsurgical trainees beginning their microsurgical practice in surgical skill laboratories. From the literature reviews, alternative suture materials that were previously reported as standard microsutures in microsurgical skill laboratories were small filaments from large braided polyfilaments, 13 spider silk, 14 fishing line, 15 and human hair.…”
Section: Discussionmentioning
confidence: 99%
“…La elección del tipo de material de sutura dependerá no sólo de si se trata de vasos o tejidos, sino de si la sutura es o no reabsorbible 4 ; por ejemplo, en el caso de sutura vascular y gastrointestinal es recomendable que sea reabsorbible 5,6 . El hallazgo durante la autopsia de cambios morfológicos de un órgano, tejido o vaso puede llevar a confusión con nódulos tumorales o metastásicos, y el diagnóstico sólo será exacto si se realiza un estudio histopatológico, como ocurrió en el caso expuesto.…”
Section: Discussionunclassified